Vouchers and Religious Schools: Why Some Religious Schools May Refuse to Participate - Mawdsley, Ralph D.; Russo, Charles J. (Catholic Education: A Journal of Inquiry and Practice, 2003)
With the recent U.S. Supreme Court decision (Zelman v. Simmons-Harris, 2002), upholding the vouchers portion of an Ohio-based scholarship program, interest in vouchers is at an all-time high. Will the availability of voucher programs create an exodus of students from public schools? Will private schools open their doors and classrooms to respond to the increasing need? Several problems remain before voucher programs can become widespread, and even then some private and religious schools may opt not to participate. This article discusses the autonomy of religious schools, summarizes relevant court cases, and explores three possible reasons why some private and religious schools may not be willing to accept vouchers.